2018
DOI: 10.1111/eff.12411
|View full text |Cite
|
Sign up to set email alerts
|

Turbid water induces refuge behaviour of a commercially important ayu: A field experiment for interstream movement using multiple artificial streams

Abstract: Riverine systems are inherently dendritic in nature, and turbid water may not necessarily flow equally throughout an entire catchment. Tributaries have the potential to serve as refugia from temporarily turbid water in the main stem. As ayu (Plecoglossus altivelis) are one of the important species for the inland fisheries industry and recreational fishing, their behaviour in a branched river network is a primary concern. We released ayu with radio‐transmitting tags into two experimental streams that joined at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…Many fish species used the temporary underwater path to actively immigrate to drainage ditches that serve as spawning and nursery habitats (Nakano, 2017). Additionally, fish species could evacuate from the disturbed downstream rivers during a flood, as previous studies showed that fish species inhabiting a mainstream actively move into tributaries or backwaters for refuge when a flood increases flow discharge and turbidity in the mainstream (Koizumi et al, 2013; Mori et al, 2018; Sumida et al, 2019; Tawa et al, 2022). Also, some fish species were likely to be passively swept away to drainage ditches by backflow of water from downstream rivers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many fish species used the temporary underwater path to actively immigrate to drainage ditches that serve as spawning and nursery habitats (Nakano, 2017). Additionally, fish species could evacuate from the disturbed downstream rivers during a flood, as previous studies showed that fish species inhabiting a mainstream actively move into tributaries or backwaters for refuge when a flood increases flow discharge and turbidity in the mainstream (Koizumi et al, 2013; Mori et al, 2018; Sumida et al, 2019; Tawa et al, 2022). Also, some fish species were likely to be passively swept away to drainage ditches by backflow of water from downstream rivers.…”
Section: Discussionmentioning
confidence: 99%
“…We would also have failed to observe fish species that evacuated from a mainstream because our sampling of fish was done not during but several days after the flood for safety and practical reasons. Indeed, previous studies showed that some fish species that once moved to tributaries during a flood returned to a mainstream as soon as the flood settled (Koizumi et al, 2013; Mori et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The response to floods may differ among fish species based on their ecology and biological characteristics. Plecoglossus altivelis is known to avoid turbid water and evacuate turbid sections [30]. The Yoshida River, which had the lowest eDNA concentration after Flood Event 1, showed high turbidity during the flood (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…The fish P. altivelis is a major fishery resource of inland fisheries in Japan; Hii River is not an exception. Fish catches of the fish has been steadily decreasing during 2000s due not only to aging and population decrease of members of inland fisheries cooperatives, but also to degradation of river environment serving as habitats, which was triggered by the flow regulations by operating huge hydraulic structures like dams [61][62]. Especially, Obara Dam is completely fragmenting habitats of aquatic species including P. altivelis because of its heigh 90 (m) as well as the lack of fish ladders.…”
Section: Target Problemmentioning
confidence: 99%